PHYTO-PHARMACOLOGY OF CELASTRUS PANICULATUS: AN OVERVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Celastrus paniculatus (CP), a traditional Ayurvedic medicinal plant used for centuries as a memory enhancing, anti-inflammatory, analgesic, sedative and antiepileptic agent. The seed extract has been extensively investigated in several laboratories for their neuropharmacological effects and a number of reports are available confirming their nootropic action. In addition, researchers have evaluated the anti-inflammatory, anticonvulsant and other pharmacological effects of CP preparations/extracts. Therefore, in view of the important activities performed by this plant, investigation must be continued in the recently observed actions described in this paper. Moreover, clinical studies have to be encouraged, also to evidence any side effects and possible interactions between this herbal medicine and synthetic drugs.